Fundamental Accounting Principles - D.Larson Kermit (McGraw -Hill, 2009)
Larson's Fundamental Accounting Principles has been setting the standard in financial accounting for over a decade and continues to keep pace with the changing needs of today's classroom. The Twelfth Canadian Edition benefits from a superior research and development process, and sets the standard in using technology to enhance teaching and learning - in and beyond the classroom. The Twelfth Canadian Edition continues to build on the core strengths that have made it a market leader - presenting accounting principles in a clear, comprehensive, and technically accurate text that has been developed in accordance with evolving market needs. New to the Twelfth Canadian Edition is the introduction of the Student Success Cycle to reinforce the learning process. Learning involves a cycle, and financial accounting is no exception. Following the steps in the Student Success Cycle will help students learn, rather than simply memorize, the basics of financial accounting. Critical Thinking Exercises have also been introduced to encourage the application of this knowledge. This text also continues to boast a superior supplements and technology package, which supports the widest range of teaching and learning, whether in a traditional or technology-enhanced classroom. Like the text, the supporting resources and technology solutions have been developed in accordance with market needs and set a new standard in Financial Accounting.